2022
DOI: 10.1001/jamainternmed.2022.4000
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Associations of Daily Step Counts and Intensity With Cancer and Cardiovascular Disease Incidence and Mortality and All-Cause Mortality

Abstract: IMPORTANCERecommendations for the number of steps per day may be easier to enact for some people than the current time-and intensity-based physical activity guidelines, but the evidence to support steps-based goals is limited.OBJECTIVE To describe the associations of step count and intensity with all-cause mortality and cancer and cardiovascular disease (CVD) incidence and mortality. DESIGN, SETTING, AND PARTICIPANTSThis population-based prospective cohort study used data from the UK Biobank for 2013 to 2015 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
111
1
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 125 publications
(120 citation statements)
references
References 42 publications
(90 reference statements)
6
111
1
2
Order By: Relevance
“…We excluded participants with missing covariates and insufficient valid wear days. Monitoring days were considered valid if wear time was greater than 16 h. To be included in analysis, participants were required to have at least three valid monitoring days, with at least one of those days being a weekend day 45,46 . We excluded participants who reported that they cannot walk.…”
Section: Online Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…We excluded participants with missing covariates and insufficient valid wear days. Monitoring days were considered valid if wear time was greater than 16 h. To be included in analysis, participants were required to have at least three valid monitoring days, with at least one of those days being a weekend day 45,46 . We excluded participants who reported that they cannot walk.…”
Section: Online Contentmentioning
confidence: 99%
“…We excluded participants with missing covariates and insufficient valid wear days. Monitoring days were considered valid if wear time was greater than 16 h. To be included in analysis, participants were required to have at least three valid monitoring days, with at least one of those days being a weekend day45,46 . We excluded participants who reported that they cannot walk.To enable examination of VILPA in our study (brief bouts of nonexercise VPA occurring during daily living), we included only participants who reported no leisure time exercise participation and no more than one recreational walk per week.…”
mentioning
confidence: 99%
“…Physical inactivity is one of the major public health issues worldwide, contributing to an estimated 3.2 million deaths and imposing $54 billion in direct health care costs annually . Several studies have used the number of daily steps as a simple and valid measure of physical activity and have investigated the association of daily steps with health outcomes, including cardiovascular disease and dementia . Recently, a meta-analysis suggested that more daily steps are associated with a steady decline in mortality risk up to approximately 8000 daily steps, at which point mortality risk appeared to plateau .…”
Section: Introductionmentioning
confidence: 99%
“…In particular, a daily step count is rather easy to collect, and may represent a useful surrogate measure of physical and ambulatory activity that is associated with relevant clinical outcome parameters [ 3 ]. For example, previous studies associated a reduced number of steps per day with relevant pathological conditions, including cancer and cardiovascular diseases [ 4 ], obesity, major depressive disorder, diabetes and hypertension [ 5 ], and in general mortality [ 6 , 7 ]. As to neurodegenerative disorders, a recent report showed the link between the daily number of steps collected through a wrist-worn accelerometer and the incidence of dementia in a large cohort of patients [ 8 ].…”
Section: Introductionmentioning
confidence: 99%